Calciferol Status and Clinical Outcomes in Children with Congenital Heart Disease after Heart Surgery - Effendy, Zulham; Rahayuningsih, Tri Yanti; Razi, Fachrul; Kurniawan, Hendra; , Azmi; Marzuki, Farhan; , Herdianta; Pratama, Rovy (Folia Medica Indonesiana, 2023)
Highlights: Calciferol has cardioprotective properties, and a severe deficiency of calciferol is associated with septic shock, a longer duration of mechanical ventilation and treatment in the intensive care unit, and mortality. The role of calciferol in critical conditions has been described in several research reports, but relatively little is known about its function in pediatric cardiac surgery. Abstract Calciferol is a micronutrient and a secosteroid hormone that plays a role in maintaining the health of bones and soft tissues in the body, such as the myocardium, as well as the immune system. Hypovitaminosis D has been reported to be associated with poor clinical outcomes and child mortality in pediatric intensive care units. Children with congenital heart disease (CHD) are vulnerable to critical conditions and require early intervention due to heart failure. This study aimed to investigate the influence of calciferol status on the clinical outcomes of pediatric CHD patients who underwent heart surgery. A systematic literature review was conducted using the electronic databases from PubMed, Elsevier, and Cochrane. This study included observational and randomized control studies that assessed the calciferol status of pediatric CHD patients undergoing cardiac surgery. From a total of 168 studies, 8 studies were selected for review. The preoperative and postoperative calciferol status as well as clinical outcomes following pediatric cardiac surgery were reviewed. According to the findings, most pediatric CHD patients suffered from calciferol deficiency prior to corrective heart surgery, which further decreased postoperatively and was associated with clinical outcomes in the intensive care unit (ICU). Preoperative calciferol supplementation has been reported to enhance serum calciferol levels and is associated with good clinical outcomes in pediatric patients undergoing cardiac surgery.